(untitled) (The Research of Medical Science Review, 2025)
Objective: To evaluate the effectiveness and accessibility of mental health services provided at Fauji Foundation Hospital, Rawalpindi, by examining client experiences, satisfaction levels, and potential barriers to accessing care, with the aim of identifying areas for improvement and enhancing service delivery. Methodology; A cross-sectional study was conducted at Fauji Foundation Hospital, Rawalpindi, in the Psychiatry Outpatient Department. The study included 374 participants, determined using the WHO sample size calculator. A structured questionnaire, divided into sections on demographics, mental health services, and provider competence, was used for data collection. Results; among participants, 68% were satisfied with mental health services. Younger clients (75%) were more satisfied than older ones (59%) (p = 0.03). Males (73%) reported higher satisfaction than females (63%) (p = 0.04). Muslim clients (71%) and urban residents (74%) were more satisfied than non-muslims (55%) and rural residents (61%) (p < 0.05). Key factors driving satisfaction included respect from staff (82%), availability of informational materials (76%), and follow-up appointments (80%). Clinic cleanliness (65%) and communication about treatment options (61%) were rated moderately and did not significantly influence satisfaction (p > 0.05). Conclusion; Client satisfaction with mental health services was influenced by demographic characteristics such as age, gender, religion, income, and urban residency. Respect from staff and the availability of informational materials were key drivers of satisfaction. However, areas such as clinic cleanliness and communication about treatment options need improvement.